AVTOMOBILSOZLIKDA ROBOTOTEXNIKANING AHAMIYATI VA DOLZARBLIGI - Kupaysinov Dostonbek Xusniddin o’g’li (Лучшие интеллектуальные исследования, 2023)
Annotation: Mechatronics and robotics is one of the most modern and prestigious specialties in the world, which incorporates artificial intelligence, cybernetics, electromechanics, electronics, and IT technologies. In particular, the role of robotics in the automotive industry is incomparable.